2018
DOI: 10.1101/281550
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genotyping Polyploids from Messy Sequencing Data

Abstract: Detecting and quantifying the differences in individual genomes (i.e. genotyping), plays a fundamental role in most modern bioinformatics pipelines. Many scientists now use reduced representation nextgeneration sequencing (NGS) approaches for genotyping. Genotyping diploid individuals using NGS is a well-studied field and similar methods for polyploid individuals are just emerging. However, there are many aspects of NGS data, particularly in polyploids, that remain unexplored by most methods. We provide two ma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 66 publications
(91 reference statements)
1
11
0
Order By: Relevance
“…In our simulations, we found that sequence depth had the largest effect on accurately estimating the genotype and admixture proportion of an individual for a given ploidal level, similar to findings in Gerard et al (2018). The degree of differentiation among demes (driven by F divergence from the ancestral population) had the second largest effect on the accuracy of genotype and ancestry estimates (as seen in Figures S2, S4 and S6, and Table S2).…”
Section: Discussionsupporting
confidence: 75%
“…In our simulations, we found that sequence depth had the largest effect on accurately estimating the genotype and admixture proportion of an individual for a given ploidal level, similar to findings in Gerard et al (2018). The degree of differentiation among demes (driven by F divergence from the ancestral population) had the second largest effect on the accuracy of genotype and ancestry estimates (as seen in Figures S2, S4 and S6, and Table S2).…”
Section: Discussionsupporting
confidence: 75%
“…Both, missing values and heterozygous undercalling, hinder linkage analysis, with a substantial impact in marker ordering and phasing, increasing the total map length. To overcome this limitation, new approaches have been developed to improve genotype calling in outcrossing species as well as to impute missing genotypes (Swarts et al, 2014;Covarrubias-Pazaran et al, 2016;Kim et al, 2016;Gerard et al, 2018). Here, we used a genotype calling method that takes advantages of the relative abundance of each allele (read counts) and the Mendelian properties of the mapping populations (Serang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…reflecting genotype uncertainty (Gerard et al 2018), but requires excessive amounts of 48 computational time to run. SuperMASSA (Serang et al 2012) and fitPoly (Voorrips et al 2011) 49 were originally designed for calling polyploid genotypes from fluorescence-based SNP assays 50 and have been adapted for sequencing data, but fail to call genotypes when low read depth 51 results in high variance of read depth ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Overview 79 polyRAD implements Bayesian genotype estimation, similar to that proposed and 80 implemented by several other groups (Li 2011;Nielsen et al 2011;Garrison and Marth 2012;81 Korneliussen et al 2014;Maruki and Lynch 2017;Gerard et al 2018;Blischak et al 2018). In 82 all polyRAD pipelines, genotype prior probabilities (P(Gi)) represent, for a given allele and 83 individual, the probability that i is the true allele copy number, before taking allelic read depth 84 into account.…”
mentioning
confidence: 99%
See 1 more Smart Citation